Mechanical properties and loading response of prestressed concrete cylinder pipes under internal water pressure. (1st August 2020) - Cheng, Bingqing; Dou, Tiesheng; Xia, Shifa; Zhao, Lijun; Yang, Jinxin; Zhang, Qi
Highlights: A full-scale test was performed to study mechanical properties and loading response of prestressed concrete cylinder pipes (PCCPs) under internal water pressure. Fiber Bragg grating (FBG) sensing technology was utilized to obtain the deformation of each component, especially the steel cylinder. The whole deformation process of PCCPs was quantified and investigated through the limit-states of ANSI/AWWA C304. The test results demonstrated that appropriate quality of materials and proper operation guaranteed trouble-free operation of PCCPs. Abstract: Prestressed concrete cylinder pipes (PCCPs) are widely used in large-scale water conveyance projects. It is important to study the mechanical properties and loading response of PCCPs to ensure trouble-free operation. There were insufficient test data pertaining to the deformation of the concrete cores (including the inner and the outer concrete core), the prestressing wire, the mortar coating, especially the steel cylinder. In this paper, a full-scale test was performed on a PCCP under internal water pressure through fiber Bragg grating (FBG) sensing technology. The test results showed that the state of PCCPs would reach three limit-states successively. Firstly, the strains of the concrete cores, the prestressing wire, the steel cylinder and the mortar coating increased linearly with the growth of the internal water pressure. The cracks in the concrete cores indicated the beginning of the serviceability limit-state. The corresponding pressure is 1.8 MPa. The growth of the internal water pressure primarily affected the steel cylinder and the prestressing wire during the continuous period. When the steel cylinder yielded at the pressure of 2.25 MPa, the pipe reached its elastic limit-state. At last, the strength of the pipe decreased obviously as the cracks propagated throughout the concrete cores. The pipe would come to the strength limit-state until the prestressing wire yielded. The test results found that the internal water pressure relieved final prestress of the inner concrete core was different from that of the outer concrete core in the embedded-cylinder pipe (ECP). It was also proved that FBG sensing technology could be the continuous monitoring system for the condition assessment of PCCPs. In particular, the test results demonstrated that the appropriate quality of materials and proper operation guaranteed trouble-free operation of PCCPs. The objective of this research is to provide experimental references for the application of PCCPs and push back safety assessment of this type of large-diameter pipes.